Pengaruh Penggunaan Mortar dan Alu Berbahan Porselen pada Preparasi Sampel Pengujian Scanning Electron Microscope Energy Dispersive X-Ray (SEM-EDX) - Sulistya, Ida Ayu Sulistya (INDONESIAN JOURNAL OF CHEMICAL RESEARCH, 2026)
Porcelain mortars and pestles are basic sample preparation tools. Scratches on porcelain mortars and pestles cause the erosion of silicon dioxide (SiO2), which is hypothesized to be the source of silicon (Si) contamination during SEM-EDX testing. This study compared unground samples, samples ground with a new mortar, and samples ground with a used laboratory mortar (exhibiting visible scratches). The SEM-EDX elemental ranges for the hydrotalcite samples across the three preparation treatments were C: 5.07%–5.38%, O: 56.54%–60.72%, Zn: 10.99%–13.64%, Mg: 13.80%–14.53%, and Al: 10.36%–10.46%. Meanwhile, the EDX elemental ranges for the sodium chloride samples were Na: 53.31%–54.91% and Cl: 45.09%–46.69%. Notably, silicon (Si) was not detected in any of the preparation treatments for either hydrotalcite or sodium chloride. The absence of detected silicon indicates that the porcelain mortar and pestle do not contribute to silica contamination within the samples.